10 minutes 38 seconds in this strange world - Shafak, Elif (Penguin Books London, 2020)
'In the first minute following her death, Tequila Leila's consciousness began to ebb, slowly and steadily, like a tide receding from the shore. Her brain cells, having run out of blood, were now completely deprived of oxygen. But they did not shut down. Not right away...' For Leila, each minute after her death brings a sensuous memory: the taste of spiced goat stew, sacrificed by her father to celebrate the long-awaited birth of a son; the sight of bubbling vats of lemon and sugar which the women use to wax their legs while the men attend mosque; the scent of cardamom coffee that Leila shares with a handsome student in the brothel where she works. Each memory, too, recalls the friends she made at each key moment in her life - friends who are now desperately trying to find her..